Survival analysis of platinum-refractory patients with advanced esophageal cancer treated with docetaxel or best supportive care alone: a retrospective study. Issue 8 (1st December 2014) - Moriwaki, T.; Kajiwara, T.; Matsumoto, T.; Suzuki, H.; Hiroshima, Y.; Matsuda, K.; Hirai, S.; Yamamoto, Y.; Yamada, T.; Sugaya, A.; Kobayashi, M.; Endo, S.; et al.
Summary: The survival benefit of second-line chemotherapy with docetaxel in platinum-refractory patients with advanced esophageal cancer (AEC ) remains unclear. A retrospective analysis of AEC patients with E astern C ooperative O ncology G roup performance status (PS ) ≤ 2 was performed, and major organ functions were preserved, who determined to receive docetaxel or best supportive care (BSC ) alone after failure of platinum-based chemotherapy. The post-progression survival (PPS ), defined as survival time after disease progression following platinum-based chemotherapy, was analyzed by multivariate C ox regression analysis using factors identified as significant in univariate analysis of various 20 characteristics (age, sex, PS, primary tumor location, etc) including G lasgow prognostic score (GPS ), which is a well-known prognostic factor in many malignant tumors. Sixty-six and 45 patients were determined to receive docetaxel and BSC between J anuary 2007 and D ecember 2011, respectively. The median PPS was 5.4 months (95% confidence interval [CI ] 4.8–6.0) in the docetaxel group and 3.3 months (95% CI 2.5–4.0) in the BSC group (hazard ratio [HR ] 0.56, 95% CI 0.38–0.84, P = 0.005). Univariate analysis revealed six significant factors: treatment, PS, GPS, number of metastatic organs, liver metastasis, and bone metastasis. Multivariate analysis including these significant factors revealed three independent prognostic factors: docetaxel treatment (HR 0.62, 95% CI 0.39–0.99, P = 0.043), better GPS (HR 0.61, 95% CI 0.46–0.81, P = 0.001), and no bone metastasis (HR 0.31, 95% CI 0.15–0.68, P = 0.003). There was a trend for PPS in favor of the docetaxel group compared with patients who refused docetaxel treatment in the BSC group (adjusted HR 0.61, 95% CI 0.29–1.29, P = 0.20). Docetaxel treatment may have prolonged survival in platinum-refractory patients with AEC .